Origin and evolution of the universe : evidence for design? - Robson, John M. (McGill-Queen's University Press, 1987)
Does the universe have the character it has because of design? In this collection of essays first presented at a symposium sponsored by the Canadian Institute for Advanced Research and the Royal Society of Canada, seventeen scientists and philosophers re-examine the "Argument by Design" in light of current scientific theories. Scientists in such diverse fields as cosmology, physics, geology, biology, and psychology provide syntheses of the state of their respective disciplines with regard to questions such as the origin or evolution of the universe and of life, the interaction of life and terrestrial environment, and verbal communication in prehumans. Contributions by philosophers cover such areas as arguments for as designer and the question of whether nature's laws and initial conditions could be viewed as "fine tuned" for the production of life. Many of the chapters demonstrate the awe-inspiring success of modern science in explaining the universe in terms of fairly straightforward natural laws, countering those versions of the design argument which try to find evidence of God's activities in the supposed failures of scientific laws to cover various phenomena. This book not only raises important questions about our understanding of the world and its origins abut also provides a fascinating view of the different perspectives on this topic